2005
DOI: 10.1080/15459620500280960
|View full text |Cite
|
Sign up to set email alerts
|

A hematology surveillance study of petrochemical workers exposed to 1,3 butadiene

Abstract: Complete blood counts (CBC) have been recognized as an easy and readily available screen for hematotoxicity following occupational exposure to 1,3-butadiene. This study evaluated hematology data from employees who have ever participated in the Shell Butadiene Medical Surveillance Program (BMSP), compared with employees who have not participated. This study examined potential hematopoietic toxicity in relation to the occupational exposures at two Shell facilities. This study included 404 employees who participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…( 4 ) have a higher confidence than original exposure estimates. Dose‐response modeling was conducted based on the updated studies by Cheng et al ( 9 ) and Sielken et al ( 10 ) A review of the scientific literature indicated there were no other epidemiology studies ( 11,12 ) that would be appropriate to evaluate human cancer risk from BD exposure.…”
Section: Introductionmentioning
confidence: 99%
“…( 4 ) have a higher confidence than original exposure estimates. Dose‐response modeling was conducted based on the updated studies by Cheng et al ( 9 ) and Sielken et al ( 10 ) A review of the scientific literature indicated there were no other epidemiology studies ( 11,12 ) that would be appropriate to evaluate human cancer risk from BD exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Few adverse noncarcinogenic effects were observed other than reproductive and developmental effects, except for increases in organ weights in rats (U.S. EPA, 2002a) and hematological effects in mice exposed to higher concentrations (i.e., ≥65 ppm). Hematological effects in mice exposed to high BD concentrations may not be relevant for humans exposed to lower BD concentrations, as demonstrated by Tsai et al (2005). Tsai et al (2005) conducted a hematology surveillance study of petrochemical workers at two Shell facilities and reported there were no significantly increased abnormalities for any hematology parameter among 404 exposed employees versus 733 controls.…”
Section: Key Studiesmentioning
confidence: 99%
“…Hematological effects in mice exposed to high BD concentrations may not be relevant for humans exposed to lower BD concentrations, as demonstrated by Tsai et al (2005). Tsai et al (2005) conducted a hematology surveillance study of petrochemical workers at two Shell facilities and reported there were no significantly increased abnormalities for any hematology parameter among 404 exposed employees versus 733 controls. Workers were exposed to mean time-weighted average (TWA) BD concentrations of 4.55 ppm from 1979 to 1996 (TWA-8, TWA-10, and TWA-12 together) and 0.25 ppm from 1997 to 2003.…”
Section: Key Studiesmentioning
confidence: 99%